Artificial Intelligence (AI) for Sustainable Development in MSMEs: A Literature Review - Usman, Maulana; Harto, Puji (Research Horizon, 2024)
Information and Communication Technology clearly showcases its advantages in this era of greater digitalization. With the enhanced technology, the application of Artificial Intelligence is anticipated in several areas, particularly within the business sector. Many sectors are affected by the digital trend, including the business among micro, small, and medium enterprises (MSMEs). The present research utilized a literature review approach to seek clarifications of the scope of AI in improving the productivity of MSMEs through operational efficiencies, innovations of products and services, and better decision making based on data analytics. This research adopts a literature review the research collects and reviews information from 34 pertinent journals published from 2019 to 2024. Data indicates that AI has the capacity to enhance productivity and resource usage however there are still daunting challenges such as costs of implementation and inadequacy of the technical infrastructure. Such conclusions are located within the issue of MSME sustainability, and using thematic analysis the article discusses the pros and cons of implementing AI. Sustaining operational sustainability through AI adoption is possible by enhancing supply chain efficacy and minimizing adverse environmental effects although policy and infrastructure enhancement can help achieve more. The implications of the research conducted urge indeed for longitudinal studies related to the long-term effects of AI on MSMEs as well as specific branches. Hence, this article presents a theoretical rationale for approaches that will focus on AIs in the context of sustainable development.